2014
DOI: 10.1186/1471-2229-14-70
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal glyphosate exposure alters flowering phenology and causes transient male-sterility in Brassica spp

Abstract: BackgroundHerbicide resistance in weedy plant populations can develop through different mechanisms such as gene flow of herbicide resistance transgenes from crop species into compatible weedy species or by natural evolution of herbicide resistance or tolerance following selection pressure. Results from our previous studies suggest that sub-lethal levels of the herbicide glyphosate can alter the pattern of gene flow between glyphosate resistant Canola®, Brassica napus, and glyphosate sensitive varieties of B. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
2
25
1
1
Order By: Relevance
“…Erosive rainfall occurs frequently in regions with loess soil in China (Shi and Shao, 2000), and many nutrients and pesticides are transported, leading to serious water pollution (Li et al, 2011;Ongley et al, 2010). Glyphosate in soil either can be dispersed in runoff and drainage or carried with soil particles (Avigliano et al, 2014;Bergstrom et al, 2011;Kjaer et al, 2005;Lanctot et al, 2013;Londo et al, 2014;Styczen et al, 2011;Webster et al, 2014). Many studies have documented the transport of glyphosate by runoff and leached discharge, but most have focused on laboratory and lysimetric methods using pots or soil columns (Bergstrom et al, 2011;Zhao et al, 2009;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Erosive rainfall occurs frequently in regions with loess soil in China (Shi and Shao, 2000), and many nutrients and pesticides are transported, leading to serious water pollution (Li et al, 2011;Ongley et al, 2010). Glyphosate in soil either can be dispersed in runoff and drainage or carried with soil particles (Avigliano et al, 2014;Bergstrom et al, 2011;Kjaer et al, 2005;Lanctot et al, 2013;Londo et al, 2014;Styczen et al, 2011;Webster et al, 2014). Many studies have documented the transport of glyphosate by runoff and leached discharge, but most have focused on laboratory and lysimetric methods using pots or soil columns (Bergstrom et al, 2011;Zhao et al, 2009;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The dynamics of soil moisture caused by heavy rains would likely indirectly affect glyphosate decay and transport with preferential flow (Coupe et al, 2012;Degenhardt et al, 2012;Todorovic et al, 2014), which would increase the risk to nearby water bodies, soils, and aquatic life (Avigliano et al, 2014;Lanctot et al, 2013;Londo et al, 2014;Webster et al, 2014). Erosive rainfall occurs frequently in regions with loess soil in China (Shi and Shao, 2000), and many nutrients and pesticides are transported, leading to serious water pollution (Li et al, 2011;Ongley et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The reduction in flowering decreased the likelihood that these plants would be pollinated by transgenic B. rapa genotypes, thereby potentially reducing their susceptibility to gene flow, and also reduced the number of B. rapa L. seeds available in the soil seed bank. Londo et al also indicated that sublethal (0.05–0.1× f.a.r.) exposure to glyphosate resulted in deformed and shortened anthers, which appeared unable to release pollen normally.…”
Section: Discussionmentioning
confidence: 96%
“…; Londo et al . ) and can have long‐term evolutionary consequences on these non‐target species. In the USA, 40% of the pesticides applied across the 400 million acres of cropland are herbicides ( US EPA ), which impose extreme selection on naturally occurring agricultural weeds (Jasieniuk et al .…”
Section: Introductionmentioning
confidence: 99%